Integration of sight word learning and repeated reading into whole language approach in remedial reading programme: a case study / Noor Hanim Rahmat - Rahmat, Noor Hanim (Institute of Research, Development and Commercialization (IRDC), 2002)
This research looks yet another altemative approach in the Remedial Reading Programme. The students were introduced to the whole Language Approach combined with the learning of sight words and repeated reading. 13 students were chosen for this programme based on the fact that they could not read. progress was seen after I week, 2 weeks, I month and finally at the end of the research. The whole language approach requires the teacher to incorporate old learning into something new. This helps students become farniliar with recurring themes. Students progressed pell because learning the sight words requires "block" remembering unlike learning thropgh the traditional phonics.